2021
DOI: 10.1037/pspi0000314
|View full text |Cite
|
Sign up to set email alerts
|

When racism and sexism benefit Black and female politicians: Politicians’ ideology moderates prejudice’s effect more than politicians’ demographic background.

Abstract: Using large samples that are nationally diverse or nationally representative (total N ϭ 44,836), this article presents evidence that citizens' prejudice does not usually benefit or undermine politicians who are from a particular demographic group, as many past studies assumed; instead, citizens' prejudice is associated with support for conservative politicians and opposition to liberal politicians, regardless of politicians' demographic background. Study 1a and Study 1b show that, regardless of the race and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…As such, these studies clarify that the growing salience of White identity politics under the epochal demographic shift, though unlikely to benefit White politicians who are racial in-group individually, may ultimately benefit White citizens collectively. Finally, recent data (Bai, 2020;Chamber et al, 2013) observed that racial attitudes about racial out-groups have a primarily "ideological" effect. Current studies contribute to and complement this line of work by demonstrating that racial identification, a racial attitude that has a focus on one's self and in-group, has an "ideological" effect as well.…”
Section: Theoretical Contributionsmentioning
confidence: 94%
“…As such, these studies clarify that the growing salience of White identity politics under the epochal demographic shift, though unlikely to benefit White politicians who are racial in-group individually, may ultimately benefit White citizens collectively. Finally, recent data (Bai, 2020;Chamber et al, 2013) observed that racial attitudes about racial out-groups have a primarily "ideological" effect. Current studies contribute to and complement this line of work by demonstrating that racial identification, a racial attitude that has a focus on one's self and in-group, has an "ideological" effect as well.…”
Section: Theoretical Contributionsmentioning
confidence: 94%
“…When explaining the association between explicit prejudice and explicit evaluation of politicians, most recent studies provide more evidence for the ideology theory of prejudice over the demographic theory (Bai, 2020). Nonetheless, exactly what aspect of political ideology is responsible for the pattern remains to be clarified.…”
Section: Prejudice and Conservatism: Inequality Or Status Quo?mentioning
confidence: 99%
“…In short, past studies suggest that racism and sexism benefit conservative candidates and undermine liberal candidates in the current political landscape because racism and sexism reflect underlying motivations that predispose one to conservatism as in the preservation of extant unequal power and status quo between different social groups (Bai, 2020;Gutierrez & Unzueta, 2021). By testing the inequality hypothesis and the status quo hypothesis, the current paper extends this line of work by PREJUDICE AND POLITICIANS further unpacking different psychological motives that contribute to the effect of racism and sexism.…”
Section: The Status Quo Hypothesismentioning
confidence: 99%
See 2 more Smart Citations